The figure of teacher expected in modern physical education - Węglarz, Józef (Health Promotion & Physical Activity, 2016)
Modern education is meant to prepare comprehensively a person to live independently in specific social and cultural realities. A part of this versatility covers preparing the student to participate in physical culture in adulthood. It is a main goal of the process of physical education. To fulfil this purpose, it is necessary to equip the student with fixed beliefs about the need to care for his body and with skills to command it. These powers (axiological and technological ones) should be supported by extensive knowledge of the needs and possibilities of the body to such an extent that all activities relating to the body are rational. It is the task of physical education teacher who is supposed to introduce the student into the world of physical culture. The teacher is expected to be the student’s guide to the world of the body’s value.